2006
DOI: 10.1530/eje.1.02205
|View full text |Cite
|
Sign up to set email alerts
|

Detection of thyroid peroxidase mRNA and protein in orbital tissue

Abstract: Objective: We have previously reported that the absence of thyroid peroxidase antibodies (TPOAb) in Graves' disease (GD) was associated with an increased risk of Graves' ophthalmopathy (GO). This observation raised the possibility that TPOAb could act as a protective factor. However, the presence of thyroid peroxidase (TPO) in the orbit has not been previously reported. The aim of this study was to confirm or exclude the presence of orbital TPO. Methods and design: Relative TPO mRNA expression from GO (nZ6) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
1
12
0
2
Order By: Relevance
“…Our experiments demonstrate that TPO mRNA and protein are not confined to thyroid cells but are also present in other tissues, albeit it at low levels. Our results confirm those of Lai et al 30 who demonstrated TPO expression in orbital tissue.…”
Section: Discussionsupporting
confidence: 93%
“…Our experiments demonstrate that TPO mRNA and protein are not confined to thyroid cells but are also present in other tissues, albeit it at low levels. Our results confirm those of Lai et al 30 who demonstrated TPO expression in orbital tissue.…”
Section: Discussionsupporting
confidence: 93%
“…A functional TSH‐R has been detected on orbital fibroblasts in in vitro and in situ studies, and a correlation between TSH‐R antibodies and the activity/severity of GO has been described 26,27 . Interestingly, other thyroid‐specific antigens such as thyroglobulin and thyroid peroxidase have also been detected in orbital tissues 28,29 . In addition, several other, probably secondary, autoantigens have been characterized in extraocular muscles (the flavoprotein subunit of mitochondrial succinate dehydrogenase, G2s, sarcalumenin, the calcium‐binding protein calsequestrin) and in orbital fibroblasts (collagen XIII).…”
Section: Pathogenesis Of Graves’ Ophthalmopathymentioning
confidence: 99%
“…26,27 Interestingly, other thyroid-specific antigens such as thyroglobulin and thyroid peroxidase have also been detected in orbital tissues. 28,29 In addition, several other, probably secondary, autoantigens have been characterized in extraocular muscles (the flavoprotein subunit of mitochondrial succinate dehydrogenase, G2s, sarcalumenin, the calcium-binding protein calsequestrin) and in orbital fibroblasts (collagen XIII). Of these, antibodies against calsequestrin and collagen XIII have been shown to be very specific and sensitive diagnostic markers of GO ( Fig.…”
Section: Pathogenesis Of Graves' Ophthalmopathymentioning
confidence: 99%
“…15 Insulin-like growth factor-1 (IGF-1), another receptor on the orbital fibroblast cells, has also been shown to induce hyaluronan synthesis, 16 while thyroid-specific antigens such as thyroid peroxidase and thyroglobulin have been detected in orbital tissues. 17,18 Finally, autoantigens in extraocular muscles (calsequestrin) and orbital fibroblasts (collagen XIII) were reported to be specific and sensitive diagnostic markers of GO. [19][20][21] It should be noted that although the autoantibody theory of GO pathogenesis is speculative as the evidence is thus far insufficient to link it fully to the clinical manifestations of GO.…”
Section: Dovepressmentioning
confidence: 99%